PENGARUH PENJUALAN BERSIH DAN BIAYA OPERASIONAL TERHADAP PAJAK PENGHASILAN BADAN TERUTANG - Sjahputra, Andri; Hunein, Hamida (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
This research aims to prove empirically the effect of net sales and operating expenses on Outstanding Corporate Income Tax. The independent variables used in the study were net sales and operating expenses while the dependent variables were owed Corporate Income Tax. This research was conducted in food and beverage sector companies listed on the Indonesia Stock Exchange (IDX) in 2016 - 2020. The research method used is descriptive quantitative. The type of data used is secondary data in the form of financial statements published by food and beverage companies listed on the Indonesia Stock Exchange (IDX) in 2016 - 2020. Samples are collected using the purposive sampling method. The number of companies used as research samples as many as 9 companies with a research period of 5 (five)years, so that as many as 45 samples were obtained. Processing data by using Eviews version 10 for windows by collecting related data then calculating net sales, operating expenses and Income Tax of owed Entities and analyzing descriptivek statisti,panel data model test, panel data regression model, classical assumption test,panel data regression analysis test, T statistical test, F statistics test, and coefficient of determination (R2). The results of the F test of net sales and operating expenses simultaneously affect pajak penghasilan badan terutang. The results of the T test variable net sales and operating expenses partially affect the Outstanding Corporate IncomeTax.